Estimates of the size-fractionated primary production of UK shelf seas from satellite - Curran, K (2018)
Estimates of size-fractionated (S-F) primary production are valuable to marine ecologists, biogeochemists and policymakers, as the productivity of individual fractions are important to populations of grazers and processes of nutrient cycling and carbon export. This thesis aims to provide a means to estimate S-F PP in UK Shelf Seas, using in situ measurements of photosynthesis-irradiance (PE) parameters to tune an existing remote sensing model of S-F PP. A large dataset from the Celtic Sea and the Western English Channel shows that photosynthetic rates of picophytoplankton are markedly higher than larger nano- and microphytoplankton, and that PE parameter values for this size fraction are higher than observed in open-ocean environments. This leads to picophytoplankton accounting for a greater proportion of shelf-sea PP than previously assumed. Bio-optical measurements conducted in the Celtic Sea allowed the correction of αBvalues and calculation of φmax using more representative S-F chlorophyll-specific absorption (aph*(λ)) spectra. However, a significant number of data gaps and lack of reliable microphytoplankton spectra necessitated using average or modelled values of aph*(λ). Testing approaches of estimating aph*(λ) revealed that using some modelled spectra produced reasonable estimates of water-column PP. However, the vertical distribution of PP changed considerably between model runs using different estimated spectra, which may hinder our ability to assess the shape of the PP profile and the contribution of subsurface populations to integrated PP. This study provides a synthesis of the largest dataset of measured S-F chlorophyll concentrations, phytoplankton PE parameters, and absorption spectra for UK Shelf Seas, incorporating data from across a variety of shelf environments in multiple years, often at weekly resolution for Western English Channel sites, allowing us to explore the relationship between the photophysiology of shelf-sea phytoplankton and environmental variables. Developing a regionally-tuned model to map S-F PP in UK Shelf Seas from space represents a useful advance in the monitoring of ecology and biogeochemistry of shelf-sea systems. λ